EFFECT of METAL PRIMERS on BOND STRENGTH of RESIN CEMENTS TO BASE METALS - Fonseca, Renata Garcia [UNESP]; dos Santos Paes de Almeida, Juliana Gomes; Haneda, Isabella Gagliardi [UNESP]; Adabo, Gelson Luis [UNESP] (Mosby-elsevier, 2009)
Statement of problem. A strong and durable bond between a metal framework and a resin-based luting agent is desired. Metal primers have been shown to be very effective on noble alloys. However, there is insufficient information about their effect on base metals.Purpose. The purpose of this study was to evaluate the effect of metal primers on the shear bond strength of resin cements to base metals.Material and methods. A total of 160 cast commercially pure titanium (CP Ti) and NiCr alloy (VeraBond II) disks were embedded in a polyvinyl chloride ring, and their surfaces were smoothed with silicon carbide papers (320, 400, and 600 grit) and airborne-particle abraded with 50-mu m aluminum oxide. Specimens of each metal were divided into 4 groups (n=20), which received one of the following luting techniques: (1) Panavia F, (2) Alloy Primer plus Panavia F, (3) Bistite II DC, or (4) Metaltite plus Bistite II DC. Forty minutes after preparation, all specimens were stored in distilled water at 37 degrees C for 24 hours and then thermal cycled (1000 cycles, 5-55 degrees C). After thermal cycling, the specimens were stored in 37 degrees C distilled water for an additional 24 hours or 6 months before being tested in shear mode. Data (MPa) were analyzed using 3-way ANOVA and the post hoc Tukey test (alpha=.05). Each specimen was examined under an optical microscope (x30), and the failure mode was classified as adhesive, cohesive, or a combination of these.Results. The only significant difference between the Panavia F and Alloy Primer plus Panavia F groups occurred in the NiCr alloy at 24 hours, at which point Panavia F demonstrated superior bond strength compared to Alloy Primer plus Panavia F (P<.001). The Bistite II DC and Metaltite plus Bistite II DC groups were not significantly different. The Bistite II DC and Metaltite plus Bistite II DC groups demonstrated significantly lower bond strength to CPTI (P<.001) than the Panavia F and Alloy Primer plus Panavia F groups, and significantly lower bond strength to NiCr alloy (P<.001) than Panavia F. The Panavia F (P<.01) and Alloy Primer plus Panavia F groups' bond strength to titanium presented a significant increase (P<.001) in shear bond strength at 6 months. In general, the groups exhibited higher shear bond strength to CP Ti than to NiCr alloy (P<.01). The failure mode was 100% adhesive for all groups.Conclusions. The metal primers did not promote an increase in adhesive bonding of resin cements to NiCr alloy and to CP Ti. Water storage had no adverse effect on the shear bond strength of the groups. The shear bond strengths to titanium were significantly higher than those to the NiCr alloy. (J Prosthet Dent 2009;101:262-268)